A formação continuada de professoras e suas implicações na qualidade da prática pedagógica da educação infantil: um estudo em uma escola da rede municipal na rede municipal de Santa Maria/RS de 2016 a 2020 - Postal, Ana Paula Quevedo (2021)
This research, from the Professional Master's Course in Public Policies and Educational Management, the Graduate Program in Public Policies and Educational Management, the Federal University of Santa Maria (UFSM-RS), research line I - Policies and Management of Basic Education- addresses the theme of continuing education of teachers of Early Childhood Education and its relationship with the quality of pedagogical practice. The study has as a general objective to analyze the importance of continuing education for early childhood education teachers in a school in the municipal network of Santa Maria, from 2016 to 2020, and discusses how this training has contributed to the qualification of pedagogical practices. For specific objectives, it is prioritized to analyze the legal documents and public policies related to the career plan and the continuing education of early childhood education teachers of the Municipal Network of Santa Maria; reflect on continuing education and contributions to pedagogical practices in Early Childhood Education. The study is based on a research of qualitative approach, of the action research type and having as research subjects the managers and teachers of early childhood education, using the techniques of semi-structured interview research with the teachers of the researched school and participant observation. The theoretical framework is organized based on the authors Minayo (2010), Thiollent (2011), Bardin (2011), Kramer (2007), Kishimoto (1999), Tardif (2000, 2002), Imbernón (2010), Campos (2006,2018), Gatti (2008), Oliveira-Formosinho (2009,2016,2018), Kuhlmann (2000). The product will be a virtual portfolio presenting the results of the research, the training path of teachers and personal testimony about their professional development, recognizing the relationship of continuing education with the qualification of pedagogical practices in Early Childhood Education.